ANALISIS KESALAHAN BERBAHASA TATARAN FONOLOGI DAN MORFOLOGI PADA PENULISAN TEKS EKSPLANASI SISWA KELAS VIII SMP PGRI 4 CIMAHI - Sri Puji Astuti (IKIP Siliwangi, 2020)
Language is an important aspect in communication activities. When communicating, the language used is not only verbal, but can also be written. At the time of writing, both writing for official activities, such as in teaching and learning activities in schools and informal activities, it is not uncommon to find errors in language. The error occurred because of the limited mastery of the language of the author, and errors in writing a word or sentence. This study aims to correct errors in punctuation, letter writing, affixation processes, and to find out the results of the analysis of the form of language errors at the phonological and morphological levels in writing explanatory texts for eighth grade students. The research method used is descriptive qualitative method. The results of this study indicate that of the 38 explanatory texts, there were 33 errors, including: 21 or 63.7% errors at the phonological level and 12 or 36.3% errors at the morphological level.